Designing In-House SARS-CoV-2 RT-qPCR Assay for Variant of Concerns - Ergoren, Mahmut Cerkez; Tuncel, Gulten; Ozverel, Cenk Serhan; Sanlidag, Tamer (Global Medical Genetics, 2022)
Variants (Alfa, Gamma, Beta, and Delta) of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) are circulating worldwide. These variants of concerns share some common mutations but they also have distinguishing mutations. These mutations affect transmissibility of virus and cause evasion from neutralizing antibodies. Monitoring and identification of circulating variants is of great importance for public health. In this study, an in-house SARS-CoV-2 reverse transcription quantitative polymerase chain reaction (RT-qPCR) kit was designed to detect variants of concerns by the World Health Organization.Primer sets and probes were designed to target presence of virus along with mutations for identifying different variants (for N501Y, HV69–70del, K417N, and T478K). Reactions were set by using commercially available master mixes without a reference dye.The RT-qPCR conditions were optimized by using commercially available ribonucleic acid samples of wild-type, Alfa, Beta, Gamma, and Delta variants. Several samples were also analyzed by the in-house kit after optimization studies. All Alfa variant and wild-type samples were also double confirmed with a commercially available variant detection kit demonstrating a 100% consistence with the in-house kit. Beta, Gamma, and Delta variants could not be confirmed with any other commercially available kits as there is not any available one in the market.SARS-CoV-2 variants are gaining importance during the pandemic and shaping the fight against the virus. RT-qPCR kits detecting different variants would provide a significant advantage while screening the population.
Keywords: severe acute respiratory syndrome coronavirus 2; COVID-19; variant of concerns; reverse transcription quantitative polymerase chain reaction; molecular diagnosis